Current utilization of microturbines as a part of a hybrid system in distributed generation technology - Ismail, M.S.; Moghavvemi, Mahmoud; Mahlia, T.M.I. (Elsevier, 2013)
Microturbines are a relatively new distributed generation technology. Combined heat and power, known as cogeneration, can be considered the most economical attractive investment in microturbines. Latest technologies and increasing energy prices are propelling this technology to the forefront. This study aims to review the current state of utilization of microturbines in distributed generation as a standalone system or within a hybrid system to supply loads. It is found that more research and development effort is needed to improve the performance of microturbines, integrate them with other energy sources and adopt standards and regulations to connect them with the utility grid. These standards shall be developed to serve all parties and take into account regional and international requirements. Furthermore, complete mathematical modeling, especially for fuel consumption is still required. The development of small scale units within the range of kilowatts for in-house use as a backup source of residential PV system is also needed.